(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article explores the effectiveness of communicative tasks in developing students’ spoken discourse in English language learning. Spoken discourse is a crucial component of communicative competence, enabling learners to express ideas fluently, interact meaningfully, and participate actively in various social and academic contexts. The study examines how communicative tasks such as role-plays, discussions, information-gap activities, problem-solving tasks, and debates enhance learners’ speaking abilities. Findings from previous studies indicate that communicative tasks increase students’ confidence, fluency, vocabulary usage, and interactional competence. The article concludes that integrating communicative tasks into language instruction creates a learner-centered environment that significantly improves spoken discourse skills.